Investigating the impact of terminal heat stress on contrasting wheat cultivars: a comprehensive analysis of phenological, physiological, and biochemical traits - Kumar, Hitesh; Chugh, Vishal; Kumar, Manoj; Gupta, Vikas; Prasad, Shambhoo; Kumar, Satish; Singh, Chandra Mohan; Kumar, Rahul; Singh, Bhupendra Kumar; Panwar, Gurusharan; Kumar, Mukul (Frontiers in Plant Science, 2023)
Terminal heat stress has become one of the major threats due to global climate change which is significantly affecting the production and productivity of wheat crop. Therefore, it is necessary to identify key traits and genotypes to breed heat-tolerant wheat. The present study was undertaken with the objective of comparing the effects of heat stress (HSE) and extended heat stress (EHSE) on phenological-physio-biochemical traits of contrasting heat-tolerant and heat-susceptible genotypes during the reproductive phase. Phenological traits exhibited significant reduction under EHSE compared to HSE. Heat-tolerant genotypes maintained balanced phenological-physio-biochemical traits, while heat-sensitive genotypes showed significant reductions under both stress regimes. Among phenological traits, DM (R2 = 0.52) and BY (R2 = 0.44) have shown a positive effect on seed yield, indicating that biomass and crop duration contributed to the yield advantage under stress. During the grain filling stage, both the normalized difference vegetation index (NDVI) and chlorophyll (Chl) exhibited consistently positive impacts on grain yield under both HSE and EHSE conditions. This could be attributed to the enhanced photosynthesis resulting from delayed senescence and improved assimilate remobilization under terminal heat stress. The biochemical activity of superoxide dismutase (SOD), peroxidase (POX), and ascorbate peroxidase (APX) was induced in tolerant genotypes under HSE. The correlation of canopy temperature with phenological-physio-biochemical traits remained static under HSE and EHSE, suggesting CT as the best selection parameter for heat tolerance. The traits showing a positive association with yield and that are less affected under stress could be used for selecting tolerant genotypes under stress environments. These tolerant genotypes can be used to develop mapping populations to decipher the genes conferring tolerance as well as to study the molecular basis of tolerance.